Analisis Atas Perlakuan Akuntansi Pendapatan Jasa Konsultan Teknik Dalam Rangka Penyajian Laporan Keuangan pada PT. Indra Karya (Persero) Survey & Investigation Division di Malang - Dewi Putri Ariana; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The company’s financial performance can be seen from the income statement. Revenue is one of the elements in the income statement that can show the success of the company’s performance in an accounting period. Because of this, the accounting treatment of income in companies affects producing financial statements that are following financial accounting standards. The accounting treatment of income specifically for the type of construction service work is regulated in PSAK No. 34. The purpose of this study was to determine the income accounting treatment applied by the company and to analyze whether it was by PSAK No. 34. PT. Indra Karya (Persero) Survey & Investigation Division is one of the branch companies engaged in technical consulting services. The method used in this study is a qualitative research method with a descriptive approach. The results showed that the revenue recognition by PT. Indra Karya (Persero) Survey & Investigation Division has complied with PSAK No. 34. Income measurement is done by measuring how much of the quantity of work has been fulfilled in one accounting period, the presentation of the company’s financial statements by presenting the income in the income group in the income statement, the company’s income disclosure by the percentage of completion method that is by PSAK No. 34 paragraphs 39.Keywords: consulting service income, accounting treatment